Study of Thoracic and Lumbar Spine Kinematics When Using Tipton Chair: A Repeated-measures Study in Healthy Young Adults - Amirsalar Jafarpisheh; Reza Osquei Zadeh; Masoumeh Zakeri; Mohsen Vahedi (University of Social Welfare and Rehabilitation Sciences, 2022)
Objective: The effectiveness of the Tipton chair on the thoracic and lumbar spine of students was evaluated in the straight upright position and careful study postures. Materials & Methods: This study was performed on 30 students (20 women and 10 men) who had no history of musculoskeletal disorders. Evaluation of changes in the angles of the thoracic and lumbar spinal was performed using an electrogoniometer on the normal and Tipton chair in the two postures of straight upright and careful study. The participants were evaluated in each posture on each chair for five minutes. Considering the resting time and questionnaire completion, the study took 30 minutes for each person. The data recorded by the electrogoniometer were analyzed through repeated measures statistical test and data of the system usability scale (SUS) questionnaire by the paired t-test in SPSS software, version 25. Results: The mean range of changes in the angles of the thoracic spine in the sagittal plane showed that the variable of chair type was not significant (P=0.072), but the variable of posture was (P=0.013). Also, regarding the mean range of change in thoracic lateral flexion, the interaction of chair and posture (P=0.048) and the chair variable with (P=0.003) had a significant difference. This difference was about a 28% reduction in the mean range of changes in the lateral flexion of the thoracic spine in the upright posture and a 10% reduction in the careful study posture in the Tipton chair compared to the normal chair. While the posture variable had no significant difference (P=0.705). Also, the mean range of changes in lumbar flexion extension showed that the chair variable (P=0.003) had a significant difference. This significant difference was about a 16% reduction in the mean range of changes in the flexion extension of the lumbar spine in the upright posture and a 43% reduction in the careful study posture in the Tipton chair compared to the normal chair. While the variable of posture (P=0.162) did not have significant differences. The study's results on lateral lumbar flexion also showed that both variables of chair and posture had a significant difference (P=0.009). The mean range of changes in lumbar lateral flexion angles in both upright and careful posture in the Tipton chair was reduced by 28% compared to the normal chair. Analysis of SUS questionnaire scores for the Tipton and normal chairs showed a significant difference between these two chairs (P=0.000). In addition, the average scores of the SUS questionnaire were 78.6 for the Tipton chair and 65.9 for the normal chair, which shows an increase of 19%. Conclusion: The results of the present study showed that the Tipton chair could reduce the average range of body angles in the thoracic and lumbar spine. Also, the study results indicated an increase in user satisfaction with the Tipton chair compared to the normal chair, in which the level of satisfaction of women is higher than men. It can be due to the difference in anthropometric dimensions between women and men.